Case study of Chinese policies on female employees’ work life balance and the effectiveness on companies - LIN, WEI (2014)
The purpose of this study is to learn the relevant Chinese policies on women’s work-life balance and their effectiveness on companies. The study is based on the research method of case study. Secondary data are main resources in the findings. Demographic conditions from National Bureau of China indicate a continuous increase in women’s employment with a higher level of women’s education. Due to the increased rate of women participate in workplaces, Chinese government issues a series of laws and regulation to protect women’s rights and interests. In order to eliminate the gender discrimination, the laws and regulations are amended. However, not all problems could be addressed by laws. The companies’ responses are used to evaluate the effectiveness of the policies. Several cases of different kinds of companies are learned, and both positive and negative responses to policies emerge. Main reasons refer to the defective legal system, lack of government supervision, and companies’ corporate culture.